Comparison of success rates of orthodontic mini-screws by the insertion method - Kim, Jung Suk (Korean Association of Orthodontists, 2012)
OBJECTIVE: The aim of this study was to compare the success rates of the manual and motor-driven mini-screw insertion methods according to age, gender, length of mini-screws, and insertion sites. METHODS: We retrospectively reviewed 429 orthodontic mini-screw placements in 286 patients (102 in men and 327 in women) between 2005 and 2010 at private practice. Age, gender, mini-screw length, and insertion site were cross-tabulated against the insertion methods. The Cochran-Mantel-Haenszel test was performed to compare the success rates of the 2 insertion methods. RESULTS: The motor-driven method was used for 228 mini-screws and the manual method for the remaining 201 mini-screws. The success rates were similar in both men and women irrespective of the insertion method used. With respect to mini-screw length, no difference in success rates was found between motor and hand drivers for the 6-mm-long mini-screws (68.1% and 69.5% with the engine driver and hand driver, respectively). However, the 8-mm-long mini-screws exhibited significantly higher success rates (90.4%, p < 0.01) than did the 6-mm-long mini-screws when placed with the engine driver. The overall success rate was also significantly higher in the maxilla (p < 0.05) when the engine driver was used. Success rates were similar among all age groups regardless of the insertion method used. CONCLUSIONS: Taken together, the motor-driven insertion method can be helpful to get a higher success rate of orthodontic mini-screw placement.